The process of nucleation amongst the early cities of central Italy in the first millennium BC - Stoddart, Simon; Breslin, Emily M.; Esposito, Carmen; Gavériaux, Fanny; Marras, Gianbattista; McLaughlin, Rowan; Motta, Laura; Prato, Ornella; Schmidt, Frijda; Zeviani, Camilla (Frontiers in Human Dynamics, 2025)
This article assesses the process of nucleation amongst the early cities of Tyrrhenian central Italy in the first millennium BC. The article examines the advantages, disadvantages and causes of nucleation. A multi-proxy and multi scalar perspective is implemented drawing on the available evidence for ancient DNA, isotopes, pedology/geoarchaeology, animal and plant remains, contextualized within the settlement archaeology. The article contains original data for settlement distribution, plant remains and stable isotopic analysis of plants.